2014
DOI: 10.17267/2238-2720revbahianaodonto.v5i1.300
|View full text |Cite
|
Sign up to set email alerts
|

Aumento Gengival Influenciado Por Drogas: Uma Revisão De Literatura

Abstract: ResumoO aumento gengival influenciado por drogas é caracterizado pelo crescimento excessivo do tecido gengival circunjacente à região das papilas interdentais. Somente nos casos mais graves é capaz de recobrir os elementos dentários e interferir na nutrição do indivíduo. Os principais fármacos associados a este tipo de alteração são: nifedipina, ciclosporina e fenitoína. As consultas de caráter preventivo são fundamentais para os indivíduos que apresentam risco de desenvolver esta alteração gengival, bem como … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…According to Mendes et al 7 , carbamazepine has been used since the 1960s and demonstrated efficacy in approximately 60% to 80% of cases. However, its prolonged use triggers complications, including tremors, drowsiness, dizziness, diarrhea, epigastralgia and changes of liver function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Mendes et al 7 , carbamazepine has been used since the 1960s and demonstrated efficacy in approximately 60% to 80% of cases. However, its prolonged use triggers complications, including tremors, drowsiness, dizziness, diarrhea, epigastralgia and changes of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Its systemic use reduces patients' symptomatology by 70%. In addition, it presents a powerful attenuating effect of dysgeusia and buccal dryness 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations